The legacy of Ronald Dworkin - Waluchow, Wilfrid J.; Sciaraffa, Stefan (New York, NY : Oxford University Press, 2016)
This work assembles leading legal, political, and moral philosophers to examine the legacy of the work of Ronald Dworkin.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: Dworkin, Ronald; Law -- Philosophy; Justice; Law